(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
It is known that the oral cavity serves as a favorable environment for the proliferation and biological activity of numerous microorganisms [1-3]. In this context, along with the positive symbiotic interactions with the soft tissues of the periodontal complex, the negative effects of representatives of the normal microflora are also observed [4-6].